KOMPARASI RASIO KEUANGAN PT. BANK CIMB NIAGA,TBK SEBELUM DAN SESUDAH MERGER - Khaira Ainil Putri; Endang Afriyeni (Jurnal Ilmiah Poli Bisnis, 2018)
The purpose of this research is to know the comparison of PT. Bank CIMB Niaga,Tbk before and after the merger. Methods of data collection is using literature study (document study) by accessing the annual financial statement of Bank CIMB Niaga through www.idx.com. with descriptive analysis as Data analysis method. This research use quantitative approach with ratio from financial statement report. The result of the research shows that by using liquidity analysis namely quick ratio, banking ratio, cash ratio, and loan to deposit ratio and by using solvability namely primary ratio and risk assets ratio, the financial performance of Bank CIMB Niaga increased after the merger. At the same time, profitability ratio analysis which namely gross profit margin, net profit margin, return on equity capital, gross yield on total assets, and net income of total assets shows that financial performance of Bank CIMB Niaga decreased after merger. This is due to the high operational costs used for business development at the time of the merger.